2022
DOI: 10.3171/2022.2.jns212887
|View full text |Cite
|
Sign up to set email alerts
|

Impact of collateral flow on cost-effectiveness of endovascular thrombectomy

Abstract: OBJECTIVE Acute ischemic stroke patients with large-vessel occlusion and good collateral blood flow have significantly better outcomes than patients with poor collateral circulation. The purpose of this study was to evaluate the cost-effectiveness of endovascular thrombectomy (EVT) based on collateral status and, in particular, to analyze its effectiveness in ischemic stroke patients with poor collaterals. METHODS A decision analysis study was performed with Markov modeling to estimate the lifetime quality-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Good CS is associated with higher chances of successful recanalization following MT, better penumbra salvage and favorable functional outcomes [16,[25][26][27][28][29][30][31][32][33]. Hence, assessing CS before treatment can aid in prognostication for AIS-LVO patients.…”
Section: Discussionmentioning
confidence: 99%
“…Good CS is associated with higher chances of successful recanalization following MT, better penumbra salvage and favorable functional outcomes [16,[25][26][27][28][29][30][31][32][33]. Hence, assessing CS before treatment can aid in prognostication for AIS-LVO patients.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a smaller body of literature has conducted a long-term assessment of expected health benefits and costs associated with AIS patients with large core infarctions 10–12. Using data from the HERMES meta-analysis, Wu et al found that EVT is more cost-effective than medical care alone, and Khunte et al stated that EVT yields higher quality-adjusted life years (QALYs) regardless of the quality of collateral circulation 11 12. However, previous cost-effectiveness analyses used data from trials that were not designed to select low ASPECTS patients.…”
Section: Introductionmentioning
confidence: 99%